Experimental model of intestinal endometriosis: pilot study - Rossini, Lucio Giovanni Battista (2015)
Aims: The objective of this study is to create an experimental model of intestinal endometriosis in pigs, which might allow better understanding of deep infiltrating endometriosis and development of new treatment techniques. As secondary objective, we intend to create endometrial implants accessible by transrectal ultrasonography (TRUS). Study Design: Surgical experimental study in swine. Place and Duration of Study: This study was performed at the Instituto de Ensino e Pesquisa do Hospital Sírio-Libanês, São Paulo, Brazil, between January 2012 and December 2012. Methodology: Two sexually mature female minipigBR pigs underwent two laparotomies (each animal). The first laparotomy was performed to implant two fragments of autologous endometrium in the rectal wall. The second one was performed thirty days later to visualize, measure and obtain tissue of the site of the implants for histopathology study. A TRUS study was performed prior to the second surgery. The Institution’s Animal Utilization Study Committee approved the study. Results: In the first laparotomy a 5-cm segment of right uterine horn was resected. The endometrium was separated from the myometrium through sub-endometrial saline injection. Two endometrial fragments (1.0 x 2.0 cm) were dissected and sutured in the intra peritoneal anterior rectal wall of the animals. Thirty days later, all implants were identified during preoperative TRUS. “En-bloc” resection of the intestinal segment with the implants was performed during the second surgery. The autologous implants of endometrium invaded the muscular layer in one of the two animals. Conclusion: We demonstrated that the creation of an animal model of deep infiltrating endometriosis with intestinal involvement is feasible through a simple surgical technique. We believe that this model can be applied in experimental and clinical studies but further studies are necessary to refine the technique.